Respuesta del cultivo de fresa (Fragaria vesca) a diferentes granulometrias de carbón vegetal y rangos de tensión de humedad del suelo bajo invernadero, en la Estación Experimental La Argelia - Trelles Agurto, Walter Leonardo (2014)
This research was conducted at La Algeria Experimental Station of the Universidad Nacional de Loja, between November 2012 and September 2013, its main objective was to generate alternatives to improve the physical conditions of the soils of the basin of Loja for the production of strawberry (Fragaria vesca) in a greenhouse using different grain sizes of charcoal and soil moisture tensions; thus, improving producers’ income. The physical conditions of the soils of the basin of Loja present serious limitations for the growth of plants such as: low aeration capacity (AC), low content of organic matter (OM), and a clay to clay loam texture, therefore the exchange of CO2 and O2 in the root zone is deficient. A completely randomized design with a factorial arrangement (3x3) with three replications was applied. The independent variables were: a) Substrate (<2 mm , 2.1 mm - 4.5 mm , 0 mm of charcoal grain size) and b) Moisture range (15 cb - 20 cb 15 cb - cb 30 and 15 cb - cb 40). Charcoal dose for all treatments was 2.0 kg/m2, except the control sample. The physical conditions of the soil were maintained in good conditions in all treatments including the control sample. The pH of the substrates was maintained in the range of slightly acidic. The CEC increased from 10.58 cmol (+) Kg-1 to 12.35 cmol (+) Kg-1 equivalent to medium, the organic matter in the substrates with charcoal remained in the mid-range and the control sample in the low-range, the electrical conductivity was 1.7 mmhos cm-1 in the substrates with charcoal, which is a poor value for the crop yield, while the control sample presented 0.8 mmhos cm-1. The nitrogen content in all substrates was in the higher range. The potassium decreased from 1.1 cmol (+) Kg-1 to 0.724 cmol (+)Kg-1 corresponding to high, this is due to the consumption of potassium by the strawberry crop is about 0.90 cmol (+) Kg-1 during its phenological phase. The phosphorus content was in excess, which hinders the absorption of Fe, Mn and Zn. Regarding the calcium content, at the beginning had 11.6 cmol (+) Kg-1, while at the end had 9.49 cmol (+) Kg-1, this decrease is because the strawberry crop demands calcium in their days of flowering and fruiting. The tension range of 15 cb to 20 cb presented a greater consumption of water with 237 mm and the lowest was 148 mm for the range of 15 cb to 40 cb. The control sample showed the highest yield with 0.719 kg/plant and is statistically different from the yield of 0.607 Kg/plant of the S1 substrate (2 mm charcoal). The benefit ratio was 1.6 in the T8 (15 - 30 cb + 0 mm charcoal).